Effectiveness of Targeted Musical Therapy on Sleep Quality and Overcoming Insomnia in Seniors - Reza Mottaghi; Ali Kamkar; Alireza Maredpoor (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: The aim of the present research was to study the effectiveness of musical therapy on the overall quality of sleep and subscales of sleep quality in seniors with primary insomnia disorder. Methods & Materials: This was an experimental study. The study sample comprised of 5000 senior members of Shiraz’s Jahandidegan adult center of which 44 subjects were randomly selected and  divided into experimental and control groups. After the collapse of 6.82 percent, 41 seniors with a mean age of 68.88 years suffering from primary insomnia disorder were chosen and analyzed using Pittsburgh Sleep Quality Index before, during, and after the treatment. The intervention was provided twice a week for a period of four weeks using targeted musical therapy, which involved soothing, refreshing, and tonic music for decreasing the level of anxiety and offering euphoria and energetic daily chorus. The SPSS 21 statistical software and covariance analysis of ANCOVA and MANCOVA were used to analyze the collected data. Results: The mean scores of the overall sleep quality before the intervention in the experimental and control groups were 13.31 and 12.95, respectively, which later changed to 7.59 and 9.73 post intervention. At three months follow-up, the scores further declined to 7.22 and 9.32, respectively. The mean of overall sleep quality after the intervention was significant at P<0.001. Conclusion: The present study showed that targeted music therapy can lead to the improvement in the overall sleep quality, daily functioning, and subjective sleep quality thereby resulting in a sharp decline in the number of sleep drugs in seniors with primary insomnia disorder. Therefore, it is highly recommended by the music therapy and mental health experts for overcoming the sleep problems in older adults.